Environment Impact on Reproductive Health (Springer Nature, 2023)
This open access book focuses on of the impact of endocrine disrupting chemicals (EDCs) on human reproduction. It comprehensively discusses the three most important topics in the field: the basic biology of EDCs; the effects of EDCs on human reproduction and human reproductive systems; and potential interventions and practical advice for dealing with the problems caused by EDCs. Presenting a translational approach to endocrine disrupting chemicals research, spanning both basic biology and clinical applications, the book provides a critical link between laboratory investigations and clinical practice. Written by international experts in the field, it is a valuable reference resource for gynaecologists, obstetricians, endocrinologists and experts in reproductive medicine, and a useful tool for anyone interested in the impact of the environment on human reproduction.